Charismatic Leadership And Digital Resilience: How Kyai Navigate Religious Moderation In Contemporary Indonesian Pesantren - Hendi Sugianto; Rofiqi Rofiqi; Zainuddin Zainuddin (Pascasarjana IAI Al-Khairat Pamekasan, 2025)
This qualitative case study investigates how kyai (Islamic scholars) in contemporary Indonesian pesantren leverage their charismatic authority to promote religious moderation while building digital resilience among students in the digital media era. Conducted across four prominent pesantren in Indonesia between October 2023 and June 2024, this research employed in-depth interviews with 4 kyai, 6 ustadz, and 8 santri, complemented by participant observation and documentation analysis. Findings reveal three critical dimensions: (1) kyai strategically employ routine religious instruction and role modeling to institutionalize wasathiyah values, transforming traditional authority into a pedagogical framework for moderation; (2) pesantren implement structured digital literacy programs and device governance policies that cultivate critical digital consumption while maintaining theological groundedness; and (3) leadership adapts through hybrid models that preserve salaf traditions while selectively integrating modern educational technologies and methodologies. This study advances theoretical understanding of religious leadership in digital contexts by demonstrating how traditional charismatic authority can be reimagined as a source of resilience rather than resistance to technological change. The research contributes novel insights into the intersection of Islamic educational leadership, counter-radicalization strategies, and digital pedagogy, offering empirically grounded frameworks for pesantren seeking to navigate the tensions between tradition and modernity while promoting moderate Islamic thought.